Influence of Cu content on microstructure, grain orientation and mechanical properties of Sn–xCu lead-free solders - Kannachai Kanlayasiri; Niwat Mookam (Transactions of Nonferrous Metals Society of China, 2022)
The effect of Cu content on the microstructure, grain orientation and mechanical properties of Sn–xCu (x=0–4.0 wt.%) lead-free solder was studied. Results showed that added Cu induced the formation of intermetallic phases. Only the η-Cu6Sn5 and ɛ-Cu3Sn phases were present in the β-Sn matrix. For all contents, the strongly preferred orientation of the β-Sn phase was formed on the {001} plane. In Sn doped with 1.0 wt.% Cu, the η-Cu6Sn5 phase exhibited the preferred orientation of {0001} plane, whereas doping with 3.0 or 4.0 wt.% Cu transformed the preferred orientation to the {010} plane. In addition, only the {0001} and planes were present in the ɛ-Cu3Sn phase. The high Cu contents contributed to an increased number of low-angle boundaries, high residual strain, tensile strength and microhardness.
Keywords: Electronic Packaging and Soldering Technologies; Advanced Welding Techniques Analysis; 3D IC and TSV technologies